Development of differentiated e-module using the AppYet application on measurement material at taruna high school - Tulung, Laila Tulisna; Lubis, Rajo Hasim (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
Merdeka Curriculum is designed to meet the challenges of 21st-century skills, focusing on student development, thus requiring differentiated teaching materials that accommodate students' interests and learning styles. This research aims to develop a differentiated e-module using the AppYet application on measurement material for X IPAS 1 students at Taruna high school in Medan, which is feasible, practical, and effective. The research method used is Research and Development (R&D) with a 4D development model that includes Define, Design, Develop, and Disseminate. The research subjects were 20 students in class X IPAS 1 at Taruna high school . The research instruments used were validation questionnaires, teacher and student response questionnaires, and validated test questions. The data analysis technique used the Likert scale to determine feasibility and practicality, and the N-gain to determine the effectiveness of the e-module. The results showed that the developed e-module was highly feasible, validated by material, media, and language experts, with an overall average of 85.92%. The practicality obtained from student responses in the large group test, was 87.35%, categorized as very practical, while the responses from the physics teacher were 90.3%, also categorized as very practical. The effectiveness of the e-module, determined using the N-gain based on pre-test and post-test results, was 0.774 or 77.4%, indicating that the e-module is effective for use in learning activities. Based on the research results, it can be concluded that the developed e-module is proven to be highly feasible, practical, and effective, thus facilitating more structured and organized learning by providing content tailored to the learning styles of each student.